Cellulose nanofiber catalyzes thermal depolymerization of polylactic acid for chemical recycling - Shazleen, Siti Shazra; Zainuddin, Norhazlin; Andou, Yoshito; Ariffin, Hidayah (American Chemical Society, 2026)
Cellulose nanofiber (CNF) has been reported to enhance the mechanical and crystallization properties of poly(lactic acid) (PLA); nevertheless, its role in PLA chemical recycling via pyrolysis remains unexplored. This study revealed that PLA incorporated with 3 wt % CNF (PLA/CNF3) exhibited a marked reduction in its thermal depolymerization activation energy to 152 kJ/mol, compared to 169 kJ/mol of neat PLA, indicating that CNF facilitated thermal depolymerization of PLA. Further investigation by pyrolysis-GC/MS showed that pyrolyzates of PLA/CNF3 contained mainly lactide (≈90%) in contrast to only 69% lactide in that of neat PLA, confirming that the addition of CNF catalyzed the thermal depolymerization of PLA into lactide. The water molecule released from the CNF accelerates PLA hydrolysis, forming −COOH-terminated oligomers in situ, which then intensify the autocatalytic degradation. This finding highlights another important role of CNF in PLA as a green catalyst for thermal depolymerization, advancing PLA chemical recycling for plastic circularity.